Poly(caprolactone)-aligned nanofibers associated with fibronectin-loaded collagen hydrogel as a potent bioactive scaffold for cell-free regenerative endodontics - Leite, Maria Luisa (2022)
Aim Guided tissue regeneration has been considered a promising strategy to replace conventional endodontic therapy of teeth with incomplete root formation. Therefore, the objective of this study was to develop a tubular scaffold (TB-SC) with poly (caprolactone)-aligned nanofibres associated with a fibronectin (FN)-loaded collagen hydrogel and assess the pulp regeneration potential mediated by human apical papilla cells (hAPCs) using an in vitro model of teeth with incomplete root formation. Methodology Aligned nanofibre strips based on 10% poly(caprolactone) (PCL) were synthesized with the electrospinning technique to produce the TB-SCs. These were submitted to different treatments, according to the following groups: TB-SC (negative control): TB-SC without treatment; TB-SC + FN (positive control): TB-SC coated with 10 mu g/ml of FN; TB-SC + H: TB-SC associated with collagen hydrogel; TB-SC + HFN: TB-SC associated with FN-loaded collagen hydrogel. Then, the biomaterials were inserted into cylindrical devices to mimic the regenerative therapy of teeth with incomplete root formation. The hAPCs were seeded on the upper surface of the TB-SCs associated or not with any treatment, and cell migration/proliferation and the gene expression of markers related to pulp regeneration (ITGA5, ITGAV, COL1A1 and COL1A3) were evaluated. The data were submitted to anova/Tukey's tests (alpha = 5%). Results Higher values of cell migration/proliferation and gene expression of all markers tested were observed in groups TB-SC + FN, TB-SC + H, and TB-SC + HFN compared with the TB-SC group (p < .05). The hAPCs in the TB-SC + HFN group showed the highest values of cell proliferation and gene expression of COL1A1 and COL3A1 (p < .05), as well as superior cell migration results to groups TB-SC and TB-SC + H (p < .05). Conclusion Aligned nanofibre scaffolds associated with the FN-loaded collagen hydrogel enhanced the migration and proliferation of hAPCs and gene expression of pulp regeneration markers. Therefore, the use of these biomaterials may be considered an interesting strategy for regenerative pulp therapy of teeth with incomplete root formation.